Chocojar Bangsawan Enterprise / Muhammad Faris Azrin Abd Ramli ... [et al.] - Abd Ramli, Muhammad Faris Azrin; Mohamad Rozmi, Muhammad Adib; Norshah Hefny, Muhammad Aqmal Shah; Zailan, Abdul Rahin (2021)
This business is focused on a collaboration of four (4) members who hold significant roles in the business, such as General Manager, Administration Manager, Marketing Manager, Operations Manager and Financial Manager. Chocojar Bangsawan Enterprise is a company that focuses on Malaysia's food production. Chocojar is a new trending snakcs and is mainly popular on the citizens of Malaysia. There is two flavours which is very interesting and ideal for everyone to buy which is dark chocolate and white chocolate flavour . The moist and crunchy texture gives this chocolate cereal the potential to be a profitable product because people particularly love food for simple items. In addition, the simple steps and ingredients give our business a lot of advantages and we are highly confident that in Malaysia our market can beeasily built and spread. To make it more appealing and interesting, by implying our creativity and modern element in this chocojar making, we decided to make some innovation. Uniqueness is one of the important things nowadays in any product that makes unique chocojar with flavor a new attraction for individuals. Based on some research into the fact that Malaysia is a developing nation and during the day it is quite busy. Normally, there is not much time for breakfast or even lunch and dinner for individuals who work during office hours and students. Therefore, they can just take a jar with variousiings with our latest invention and go to work. Simple and quick as that. We are venturing into the food industry based on the goals above. Production in chocojar has the potential to be a successful company if it is achieved on a large scale and systematically handled in a modern way and this snack is suitable for any age layer to eat and enjoy. In the near future, we expect our company to become more established because with the latest innovation in our chocojar with any interesting flavoring, not only would demand increase on every occasion, but it couldbe a fresh daily snack. This will give us more benefits in order to make our brand more sustainable and stable in the long term. iv